2019
DOI: 10.3390/ma12193056
|View full text |Cite
|
Sign up to set email alerts
|

Load-Bearing Capacity of Zirconia Crowns Screwed to Multi-Unit Abutments with and without a Titanium Base: An In Vitro Pilot Study

Abstract: The static and dynamic load-bearing capacities and failure modes of zirconia crowns screwed to multi-unit abutments (MUAs) with and without a titanium base (T-base) were determined. Thirty-six monolithic zirconia crowns screwed to straight MUAs torqued to laboratory analogs (30 Ncm) were assigned to two groups (n = 18). In group A, the zirconia crowns were screwed directly to the MUAs; in group B, the zirconia crowns were cemented to the T-base and screwed to the MUAs. All specimens were aged in 100% humidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(35 reference statements)
0
4
0
1
Order By: Relevance
“…Heller et al conducted a study using straight transmucosal abutments restored by crowns cemented to titanium bases while in another group placing the crowns directly onto the transmucosal abutment. The study concluded that both types of restorations were viable treatments that did not represent a statistically significant difference [20]. Titanium base designs play a major role in their uses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Heller et al conducted a study using straight transmucosal abutments restored by crowns cemented to titanium bases while in another group placing the crowns directly onto the transmucosal abutment. The study concluded that both types of restorations were viable treatments that did not represent a statistically significant difference [20]. Titanium base designs play a major role in their uses.…”
Section: Discussionmentioning
confidence: 96%
“…For both groups, occlusion blocks 18 were constructed over the final casts for bite registration. After bite registration, the case was ready for scanning, 19 designing, 20 nesting, 21 and milling 22 (Figure 5).…”
Section: Framework Constructionmentioning
confidence: 99%
“…After bonding, the specimens were stored at 37°C under 100% humidity for 1 month, followed by 1,000 cycles of thermocycling between 5°C and 55°C with a 30-second dwell time. 10 , 11 …”
Section: Methodsmentioning
confidence: 99%
“…21,44 İmplantlar arası açısal farklılıklar ile birlikte implant sayısının fazla olduğu durumlarda multi-unit abutment'lar daha avantajlıdır. 1,45 17 İmplant sistemine bağlı olarak ölçü transfer kopingleri farklı şekillerde, uzunluklarda, genişliklerde, retansiyon sistemlerinde ve derinliklerde olabilir. 47 İmplant üstü ölçülerde direkt teknikte genelde kare ölçü kopingleri kullanılırken indirekt teknikte konik kopingler implant üzerinde kalır ve laboratuvar analoğu ile birleştirilerek çalışma modeli elde etmek amacıyla model dökülür.…”
Section: Abutment Seviyesinde öLçüunclassified